Prospective trial on telemonitoring of geriatric cancer patients using handheld devices = Prospektive Studie zum Telemonitoring mit Smartphones bei geriatrischen Krebspatienten - Bürgy, Daniel; Siefert, Victor; Neumaier, Christian; Ganslandt, Thomas; Sperk, Elena; Blessing, Manuel; Hesser, Jürgen; Welzel, Grit; Wenz, Frederik; Giordano, Frank Anton (Strahlentherapie und Onkologie, 2020)
Randomized trials indicate that electronic or app-based assessment of patient-reported outcomes may improve outcomes in cancer patients. To analyze if an app-based follow-up would be accepted by elderly cancer patients, we conducted a single-center prospective feasibility study (NCT03196050).
Published online: 18 November 2019
Gesehen am 15.04.2020